Comparison of outcomes in open-door laminoplasty versus laminectomy and instrumented fusion in patients with ossification of the posterior longitudinal ligament involving multiple levels - Islam, M. Anowarul; Ahmed, Zafri; Saha, Asim Kumar; Islam, Afia Ibnat; Aziz, Sanjida; Sarker, Sagor Kumar (International Journal of Research in Orthopaedics, 2025)
Background: This study aims to determine, in cases of multi-level ossification of the posterior longitudinal ligament (OPLL), expansive open-door laminoplasty (LP) is a better option than laminectomy and instrumented fusion (LMF). Methods: A total of 44 cases were included and divided into group LP (n=22) and group LMF (n=22). Patients, who underwent surgical treatment for continuous and mixed type multi-level OPLL between January 2010- December 2021 were retrospectively reviewed. The cervical lordosis was evaluated by C2-7 Cobb angle and cervical sagittal balance by C2-C7 sagittal vertical axis (SVA). Range of motion (ROM), Japanese Orthopedic Association (JOA), visual analog scale (VAS) and neck disability index (NDI) were used to assess clinical outcomes. Results: The LP group had significantly lower blood loss (280±50 ml vs. 450±70 ml) and shorter operative time (120±15 min vs. 160±20 min) compared to LMF. LP preserved cervical lordosis (4±1.5° vs. 7±2°, p=0.001) and ROM (8±2° vs. 14±3°, p=0.003) more effectively. NDI improvement was greater in the LP group (27±5 vs. 20±6, p=0.021). OPLL progression was higher in LP (1.2±0.3 mm vs. 0.5±0.2 mm, p=0.017). LP was associated with higher postoperative kyphosis (32% vs. 14%, p=0.038) and kyphotic change rate (28% vs. 10%, p=0.029), but lower incidence of axial pain (14% vs. 27%, p=0.043). Conclusions: Compared with the LMF, the LP is recommended for cases with OPLL and straight cervical lordosis ensuring comparable neurological recovery, improved neck ROM, less axial pain and better neck function improvement. The stabilization obtained by adding instrumented fusion could suppress progression of OPLL thickness.